School-Based Management, School Decision-Making and Education Outcomes in Indonesian Primary Schools - Chen, Dandan (2012)
This paper examines the key aspects of the practices of school-based management in Indonesia, and its effect on education quality. Using a conceptual framework of an accountability system of public service delivery, the paper explores the relations among Indonesian parents, school committees, schools, and government education supervisory bodies from three tenets: participation and voice; autonomy; and accountability. Using the data from a nationally representative survey of about 400 public primary schools in Indonesia, the paper finds that the level of parental participation and voice in school management is extremely low in Indonesia. While the role of school committees is still limited to community relations, school facilities, and other administrative areas of school management, school principals, together with teachers, are much more empowered to assert professional control of the schools. The accountability system has remained weak in Indonesia's school system, which is reflected by inadequate information flow to parents, as well as seemingly low parental awareness of the need to hold schools accountable. The accountability arrangement of the Indonesian school system currently puts more emphasis on top-down supervision and monitoring by government supervisory bodies. The findings show that although the scope of school-based management in Indonesia is limited, it has begun to help schools make the right decisions on allocation of resources and hiring additional (non-civil servant) teachers, and to create an enabling environment of learning, including increasing teacher attendance rates. These aspects are found to have significantly positive effects on student learning outcomes.